Strategies for the development of the sweetpotato early generation seed sector in eastern and southern Africa - Rajendran, S.; Kimenye, L.N.; McEwan, M. (Walter de Gruyter GmbH, 2017)
Smallholders in Eastern and Southern Africa (ESA) have limited access to timely availability of quality sweetpotato seed which contributes to sub-optimal root yields. To enhance availability and access to quality seed it is necessary to link formal plant breeding efforts to a sustainable seed supply system by means of identifying business opportunities for sweetpotato Early Generation Seed (EGS) producers. In most ESA countries, public institutions have the sole mandate for EGS production, but have not adopted an explicit business orientation. The study used primary information collected from business plans prepared by eight National Agricultural Research Institutions (NARIs) in seven countries in ESA. This study first analyzed the overall business opportunities for public institutions using a Strengths, Weaknesses Opportunities, and Threats (SWOT) tool and then a Threats, Opportunities, Weaknesses and Strengths (TOWS) approach was used to transform the SWOT results into strategies for the further development of the early generation seed sector. It was concluded that over a five to ten year period, the NARIs do have a business case for production of sweetpotato EGS. However, to capitalise on this NARIs and policy makers need to take up the recommendations from the TOWS analysis to refine strategies for exploiting opportunities in the business environment and for mitigating weaknesses to reduce vulnerability to any identified threats to the potential business in EGS.